Recent Developments in Ionic Liquid-Assisted Topical and Transdermal Drug Delivery - Ali, M.K. (Springer, 2022)
Ionic liquids (ILs) have attracted growing interest as designer solvents/materials for exploring unrealized functions in many areas of research including drug formulations and delivery owing to their inherent tunable physicochemical and biological properties. The use of ILs in the pharmaceutical industry can address challenges related to the use of conventional organic solvent-based chemical permeation enhancers. Their tunability in forming ion pairs with a diverse range of ions enables the task-specific optimization of ILs at the molecular level. In particular, ILs comprising second- and third-generation cations and anions have been extensively used to design biocompatible drug delivery systems to address the challenges related to conventional topical and transdermal drug delivery, including limited permeability, high cytotoxicity, and skin irritation. This review highlights the progress in IL-related research with particular emphasis on the very recent conceptual developments in transdermal drug delivery. Technological advancement and approaches for the formation of IL-based topical and transdermal delivery systems, as well as their promising application in drug delivery, are also discussed. Â© 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.